Three States of Wax - Parra Cancino, Juan (2024)
guitar, trumpet, and electronics.
Lecture, workshops, and performance of Three States of Wax (Juan Parra Cancino, guitar + electronics & Jonathan Impett, trumpet + electronics) at the Icelandic University of the Arts, and the Intelligent Instruments Lab.
FRIS
Editorial review
Keywords: Music, Thought and Technology